Lens Epithelium-derived Growth Factor/p75 Qualifies as a Target for HIV Gene Therapy in the NSG Mouse Model - Vets, Sofie (Nature Publishing Group, 2012)
Lens epithelium-derived growth factor (LEDGF/p75) is an essential cofactor of HIV integration. Both stable overexpression of the C-terminal part of LEDGF/p75 (LEDGF(325–530)) containing the integrase (IN)-binding domain (IBD) and stable knockdown (KD) of LEDGF/p75 are known to inhibit HIV infection in laboratory cell lines. Here, primary human CD(4)(+) T-cells were transduced with lentiviral vectors encoding LEDGF(325–530), the interaction-deficient mutant LEDGF(325–530)D366N, or a hairpin depleting LEDGF/p75 and challenged with HIV. Maximal protection of primary T-cells from HIV infection was obtained after LEDGF(325–530) overexpression reducing HIV replication 40-fold without evidence of cellular toxicity. This strategy was subsequently evaluated in the NOD.Cg-Prkdc(scid) Il2rg(tm1Wjl)/SzJ (NSG) mouse model. Threefold reduction in mean plasma viral load was obtained in mice engrafted with CD(4)(+) T-cells expressing LEDGF(325–530) in comparison with engraftment with LEDGF(325–530)D366N cells. Four weeks after transplantation with LEDGF(325–530)D366N cells, 70% of the CD(4)(+) cells were lost due to ongoing HIV replication. However, in mice transplanted with LEDGF(325–530) cells only a 20% decrease in CD(4)(+) cells was measured. Liver and spleen sections of LEDGF(325–530) mice contained less HIV than LEDGF(325–530)D366N mice as measured by p24 antigen detection. LEDGF(325–530) overexpression potently inhibits HIV replication in vivo and protects against HIV mediated cell killing of primary CD(4)(+) T-cells.